The Impact of Female Directors on Firm Performance and Investment – A Pakistani Perspective - Chaudhary, Musaab (2022)
This dissertation is focused on Corporate Governance in Pakistan. The SECP has recently introduced a comply-or-explain based approach in 2019. The new regulation has called for an increase in the number of female directors that must be on a board for a public company in Pakistan. Ergo, this dissertation investigates the impact of Female Directorships on Firm Performance and Firm Investment and provides empirical evidence from data from Fiscal Years 2019, 2020, and 2021 – the latest available data. My research finds that male directorships have a significant impact on firm performance, while female directorships do not; this is likely due to the lack of employable female directors in the Pakistani market and the intrinsic sense of nepotism, that is prevalent due to the heavily family centric ownership structure. Additionally, this dissertation also finds that Firm Investment has a significantly negative relationship with both, male and female directorships. As more directors are appointed, investment decisions are subjected to increased scrutiny, and this can reduce the overconfidence bias in CEOs. Since the latest Code of Corporate Governance was introduced in 2019, no empirical research-based studies are available. Moreover, while there is some research on Governance in Pakistan, most of it was conducted long ago and this empirical study contributes to the academic literature regarding Governance in Pakistan. In the absence of research, this dissertation helps understand and evaluate the effectiveness of female directorships, and sheds light on areas that would enhance governance and subsequent research in this regard.